(untitled) (ACME, 2023)
Initially, the essay sketches a brief aesthetic-artistic history of the cloud, from the archè of the pre-Socratic naturalistic philosophy, in which clouds are shown as a perfect compendium of life and its changing image, to the Kantian thesis on the cloudy origin of the cosmos. The clouds are images through which is evoked the structure of which is made every form that has in itself the laws of appearance and matter. They represent, therefore, an origin without origin and the complex analogical and linguistic relationship with reality. Starting from these considerations, the paper analyzes Equivalents (1993) by the Brazilian artist Vik Muniz in an analogical way. These works intensify the reflection on seeing and on existence, questioning the principles of photography and opening up to new practices that are no longer photographic but forographic. The clouds demonstrate how art is not an attempt to seek beauty but to have the courage to receive it, constantly soliciting new and changing languages.